IMBIBITION WATER-OIL RELATIVE PERMEABILITY: INTRODUCTION OF WETTABILITY STRENGTH FOR ENHANCING MODEL ROBUSTNESS - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2019)
Water-oil relative permeabilty information of hydrocarbon reservoir rocks plays important roles in various modeling activities related to reservoir modeling and production forecast. The imbibition relative permeability scheme - the process of concern in this study affects many dynamic processes in reservoir. Water flooding and water encroachment form aquifer to oil zone in the reservoir are two two examples which representation in reservoir model requires the data. This study uses the standard Corey relative permeability model as a tool to study and model imbibition relative permeability behaviour of some reservoir rocks in Indonesia. Laboratory data from as many as 340 rock samples - sandstones and limestones - of various permeability and wettability from various oil fi elds in Indonesia is used. Activities in the modeling has pointed out the need to introduce two new empirical factors that relate to rock wettability and non- wetting fl ow hindrance to the model. The two factors appear to have signifi cantly improved the ability of the model to agree and match to the measured data. The modeling also produces suggested values of the factors for rock groups based on rock wettability type and strength, as well as on permeability categories. Comparison between modeling results before and after modifi cation has shown signifi cant improvement in validity of output.